(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Street vendors are micro-enterprises that make a significant contribution to the regional economy. However, many businesses still face challenges in financial management, particularly related to cost recording and cash management, which impacts business performance. This study aims to analyze the role of cost accounting and cash management literacy in improving the business performance of chicken street vendors in Tigaraksa. The study used a quantitative approach with a survey method. Data were collected through questionnaires distributed to chicken street vendors operating in the Tigaraksa area. The variables studied included cost accounting literacy, cash management, and business performance. Data analysis was conducted using descriptive statistics and regression analysis to examine the relationships between variables. The results show that cost accounting literacy plays a crucial role in helping businesses understand cost structures, determine appropriate selling prices, and control business expenses. Furthermore, good cash management enables businesses to manage cash flow effectively, thereby maintaining liquidity and business continuity. The research findings indicate that cost accounting and cash management literacy have a positive contribution to improving business performance, as demonstrated by sales growth, increased profits, and the business’s ability to cope with financial risks. This research implies that continuous capacity building for business actors through education and training in cost accounting and cash management is necessary to support the development of more productive and competitive micro-enterprises